2018
DOI: 10.1080/20016689.2018.1542920
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcome claims in European and United States orphan drug approvals

Abstract: Purpose: We aimed to evaluate the rate of usage and the kind of patient-reported outcome (PRO) claims in orphan drug approvals from the European Medicines Agency (EMA) dated between 1/1/2012 and 31/12/2016 and to compare them to those from the US Food and Drug Administration (FDA).Methods: Orphan drug approval documentation was obtained from the EMA website. PRO-related language was extracted from the Summaries of Product Characteristics (SmPCs). Data were compared to a previously published analysis of the FDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…While decision-making bodies have historically marginalized PRO tools and the patient experience data they generate, these are now included in regulatory guidelines to support labeling claims. 47,48 Furthermore, PROs can provide comprehensive data and important nuances to inform the risk-benefit profile of a new product, particularly in rare diseases such as hemophilia where trial populations may be smaller than ideal 49 ; they could also provide more accessible and relevant data for PWH to enable shared decision-making. 50 However, studies are needed to develop GT-specific PRO tools in PWH or adapt existing tools for PWH receiving GT.…”
Section: Discussionmentioning
confidence: 99%
“…While decision-making bodies have historically marginalized PRO tools and the patient experience data they generate, these are now included in regulatory guidelines to support labeling claims. 47,48 Furthermore, PROs can provide comprehensive data and important nuances to inform the risk-benefit profile of a new product, particularly in rare diseases such as hemophilia where trial populations may be smaller than ideal 49 ; they could also provide more accessible and relevant data for PWH to enable shared decision-making. 50 However, studies are needed to develop GT-specific PRO tools in PWH or adapt existing tools for PWH receiving GT.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some countries and regions, such as the European Union and United States, have made increasing efforts to incorporate the patient voice into drug development. Between 2012 and 2016, orphan drug approvals by the European Medicines Agency and U.S. Food and Drug Administration were mainly focused on rare drugs, with 21.7% and 9.0% of all approved orphan drugs applying for PROs, respectively [ 57 , 58 ]. Therefore, the use of PROs should be expanded to include studies of reported outcomes in patients with GD in order to better help patients in making decisions about disease management and health technology assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a study looking into establishing the use of PROs in the approval of orphan medicines, revealed that, in the European context, PRO use in orphan medicines was lower when compared with all medicines’ approval. Nonetheless, when compared to the results from a similarly conducted study in the United States of America, the authors state that FDA approvals included significantly less PROMs in their processes in comparison with the EMA approvals, during the study period ( 60 ). This could be due to a relatively longer experience within the European context following the publication in 2005 of the HRQoL guidance, which suggests that regulatory guidance can stimulate the use of PROs ( 60 , 61 ).…”
Section: Patient Experience Data Use In Medicines’ Life Cyclementioning
confidence: 90%